Metabolomics revealed that toxic cyanobacteria stress reduced the flavor quality of Bellamya aeruginosa - Huang, Yuqi; Zhang, Jinjie; Xu, Dalun; Ren, Xiaohui; Yang, Wen; Lu, Kaihong; Zhu, Jinyong (Frontiers in Sustainable Food Systems, 2024)
The environmental impact of increased eutrophication and frequent cyanobacterial blooms on the growth and reproduction of aquatic organisms has become increasingly prominent in recent years. Bellamya aeruginosa is a nutrient-rich aquatic snail consumed by humans, and environmental changes may decrease its meat quality. However, the specific characteristics of muscle metabolism and flavor quality in freshwater snails and their response patterns to bloom-forming cyanobacterial stress have not been reported. Therefore, in this study, alterations in metabolites in the snail muscle after following feeding on toxic Microcystis aeruginosa were investigated using untargeted metabolomics. A total of 1,128 metabolites were identified, and the metabolic pathways of unsaturated fatty acid biosynthesis and purine, glutathione, and glycerophospholipid metabolism in snails fed toxic cyanobacteria differed from those in snails fed Chlorella vulgaris. Quantitative analysis showed increased levels of bitter-free amino acids, such as tyrosine, phenylalanine, and histidine, after consuming toxic cyanobacteria for 42 d, whereas a relative decrease was observed in the levels of umami- and sweet-free amino acids, such as glutamic acid, aspartic acid, serine, threonine, and glicine. The muscles of snails fed toxic cyanobacteria exhibited higher hypoxanthine and hypoxanthine nucleoside and lower adenosine triphosphate, adenine nucleotide, adenine nucleoside diphosphate, and hypoxanthine nucleotide contents than those of snails fed C. vulgaris. Furthermore, increased metabolites, such as stearic acid, palmitic acid, and cytidine diphosphate choline, and decreased metabolites, such as docosapentaenoic acid, docosahexaenoic acid, adrenoic acid, and L-glutamic acid, reflect the harmful effects of toxic cyanobacteria on the nutritional value and flesh quality of B. aeruginosa. This study comprehensively evaluated the effects of cyanobacterial blooms on freshwater gastropods, providing an important theoretical basis for the quality, safety, and sustainable development of snails as food and related processing industries.